ARSITEKTUR DAN PERMUKIMAN KELOMPOK SOSIAL TERPINGGIRKAN DI KOTA DENPASAR - -, Sulistyawati (Jurnal Natah, 2007)
Architectural picture of a dwelling area can indicate its social, economic, and cultural features of thecommunity concerned. Indonesia, as one of developing countries, for example, has many dwelling areasfor marginalized social groups one of them is Denpasar that often creates architecturally disordered city.The purposes of this paper are to know and understand: (1) the causes of disorder of marginalizeddwelling; (2) the negative impacts of the disorder; (3) the solutions for architectural ordering of thatdwelling; and (4) the obstacles in implementation of ordering program and its alternative solutions.The findings of this study indicate that the causes of layout and environment disordering of marginalizedgroup in Denpasar are: that this marginalized group is out of planning and facilities development of thecity; most of these poor groups earn their livings in informal sector, adding with various small familybusinesses in very narrow house yard that make supporting facilities crowded and mixed with industrialdisposal they create; they tend to choose to live in the cheapest areas and close to the center of the city, nomatter how slump it is. Other cause is culture of poverty.Its negative impacts are: hampering of the beauty of the city and waste of resources; sources of variousepidemic sicknesses; sources of psychological or mental sicknesses such as hate of staying at home andsocial emotional sensitive. The ordering solutions need the roles of all concerned, particularly relatedinstitutions, non government organizations those concern with the problems of slump areas, either fromtechnique-technological or socio-cultural points of views, with active participation of the society of thatslump area. The impeding factors to the implementation of the programs are: the obstacle from the policymakers, solved through mental improvement and understanding the needs of the city poor. The obstaclesfrom the target society and its alternatives to be solved include: land right, the determination to stay,poverty, personal characteristic and behavior of the social group.